2023
DOI: 10.1002/adfm.202215189
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing Energy Barrier in Intermediate Connection Layer for Monolithic Tandem WPeLEDs with Wide Color Gamut

Abstract: Perovskite light‐emitting diodes (PeLEDs) show promising prospects in the wide color gamut display owing to their ultra‐narrow full width at half maximum (FWHM). However, up to now, all perovskite white LEDs integrated by standard red, green, and blue perovskite emitters, namely, monolithic white PeLEDs (WPeLEDs), have been rarely reported, owing to facing some issues, e.g., solvent incompatibility in solution technique, ion exchange, and energy transfer between different emission centers. Herein, centered on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Researchers have explored many methods to obtain white light PeLEDs, such as rare-earth ions [350][351][352][353][354][355][356][357][358][359] (Yb 3+ , Eu 3+ , Sm 3+ and Tb 3+ ) doped perovskite, [4,360,361] heterophase perovskite [76] and tandem devices. [18,362,363]…”
Section: White Lightmentioning
confidence: 99%
“…Researchers have explored many methods to obtain white light PeLEDs, such as rare-earth ions [350][351][352][353][354][355][356][357][358][359] (Yb 3+ , Eu 3+ , Sm 3+ and Tb 3+ ) doped perovskite, [4,360,361] heterophase perovskite [76] and tandem devices. [18,362,363]…”
Section: White Lightmentioning
confidence: 99%
“…[1][2][3] Currently, commercial wLEDs can be classified into two categories: optically excited devices utilizing blue LEDs with PL phosphors, and electrically excited devices based on red-green-blue (RGB) units. [4][5][6][7][8] Benefited from their size-tunable luminescent wavelengths and of 50 cd m −2 based on thermally evaporated Cs 2 Na 0.4 Ag 0.6 InCl 6 microcrystals (MCs) film with trace Bi 3+ doping; [18] Qu et al successfully fabricated Cs 2 AgIn 0.9 Bi 0.1 Cl 6 QDs wLEDs with a promoted luminance of 158 cd m −2 and EQE of 0.08% by triphenylphosphine oxide passivation; [22] Chen et al demonstrated the first solution-processed EL devices using the Cs 2 AgIn 0.9 Bi 0.1 Cl 6 DP nanoplatelets (NPLs) as the sole emitting component, showing a maximum luminance of 58 cd m −2 and EQE of 0.01%. [23] Despite these rapid progresses, realizing efficient broadband white EL based on STE recombination of DP remains challenging owing to low PLQYs, high-content defect states, high nonradiative transition probabilities, and poor charge mobilities within DP.…”
Section: Introductionmentioning
confidence: 99%
“…[14] However, the hetero-phase is commonly accompanied by poor charge transport properties, [19,20] and achieving precise regulation of the hetero-phase composition is challenging, making it difficult to fabricate high-performance WLEDs. Very recently, Zeng et al reported all-perovskite tandem WLEDs with a relatively low EQE of 0.5%, [11] which could be ascribed to the severe electroluminescence (EL) discrepancy between the PeLED units and the technique incompatibility between the evaporation of organic layer and spin-coating of perovskite film. Subsequently, hybrid WLEDs incorporating mixed perovskite and organic emitting layers have been investigated as an alternative to obtaining all-perovskite WLEDs.…”
Section: Introductionmentioning
confidence: 99%
“…To date, all of the reported perovskite‐based WLEDs can be divided into all‐perovskite WLEDs and perovskite‐based hybrid WLEDs. [ 9–17 ] To avoid the damage caused by multi‐layer deposition, Li et al. reported perovskite‐based WLEDs by adopting a blue/UV LED light source to excite green and red perovskite quantum dots.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation